2001
DOI: 10.21836/pem20010103
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomographic evaluation of the distal aspect of the deep digital flexor tendon (DDFT) in horses

Abstract: Computed tomographic evaluation of the distal aspect of the deep digital flexor tendon (DDFT) in horsesThe objective of this study was to image the deep digital flexor tendon (DDFT) in its normal position by means of computed tomography from distal aspect of the proximal phalanx (P1) down to the flexor surface of the distal phalanx (P3) in 10 predefined cutting planes. A total of 30 front extremities of randomly selected Warmblood horses were used. Criteria for evaluation were differntiation of the DDFT from s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 3 publications
0
20
0
Order By: Relevance
“…Magnetic resonance (MR) imaging allows assessment of soft tissues within the hoof capsule and findings have been associated with histopathologic abnormalities 5–10 . Computed tomography (CT) is also useful for evaluation of bone and soft tissue abnormalities within the foot 11–13 . Contrast‐enhanced CT has been proposed as a means of evaluating osseous and soft tissue structures of the foot for diagnosing the cause of heel pain 14,15 …”
Section: Introductionmentioning
confidence: 99%
“…Magnetic resonance (MR) imaging allows assessment of soft tissues within the hoof capsule and findings have been associated with histopathologic abnormalities 5–10 . Computed tomography (CT) is also useful for evaluation of bone and soft tissue abnormalities within the foot 11–13 . Contrast‐enhanced CT has been proposed as a means of evaluating osseous and soft tissue structures of the foot for diagnosing the cause of heel pain 14,15 …”
Section: Introductionmentioning
confidence: 99%
“…2008). Nevertheless, several studies in the past decade have shown increasing interest in CT for soft tissue assessment as well (Tietje et al . 2001; Nowak 2002; Eliashar et al .…”
Section: Discussionmentioning
confidence: 99%
“…Lesions of the PTA have been widely documented using histology (Blunden et al ,b, 2009, radiography (Wright 1993;Dik et al 2001;Dyson 2008), nuclear scintigraphy (Dyson and Murray 2007b,c), computed tomography (CT) (Tietje et al 2001;Nowak 2002;Eliashar et al 2006;Desbrosse et al 2008) and magnetic resonance imaging (MRI) Dyson et al 2003aDyson et al ,b, 2005Busoni et al 2004Busoni et al , 2005Mair et al 2005;Murray et al 2006a,b;Dyson and Murray 2007a;Sherlock et al 2008;Bell et al 2009;Blunden et al 2009). The routine use of ultrasonography and now MRI has demonstrated the importance of soft tissue lesions in horses presenting with PTS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasonography of the foot is limited to the sagittal midline and off incidence artefacts may confuse interpretation (Denoix, 2000; Sage and Turner, 2000; Busoni and Denoix, 2001;). 3D computed tomographic (CT) studies enable more accurate evaluation of both osseous and soft tissue lesions, but require general anaesthesia (Tietje, 1995; Ruohoniemi and Tevahartiala, 1999; Tietje et al., 2001; Tucker, 2001). Nuclear scintigraphy provides highly sensitive information about abnormal bone activity, but anatomical localization is limited and there is a relative high incidence of false‐positive results (Dyson, 2002).…”
Section: Introductionmentioning
confidence: 99%